The Leadership of Phineas Taylor Barnum in the Greatest Showman Movie - Tati Mardewi; Endah Sofyan; Furi Indriyani; Nurmala Dewi (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
The objective of this research is to analyze the leadership of Phineas Taylor Barnum that exists in the main character of The Greatest Showman movie. Leadership is an important part of an organization. Leadership is the process by which an individual influences a group of people to achieve a goal. This musical movie tells the story of a circus founder, Phineas Taylor Barnum with a leadership attitude. In this descriptive qualitative study, the writers collect the data from the scene and the conversation in the movie and material with a variety of resources such as books, journals, articles, and other references. After watching the movie repeatedly and collecting the data by paying attention to the conversation in the movie's scenes, the writers study the whole story before continuing to the next step, then analyzing what the story is all about. The types of leadership that were found in this movie are (1) Democratic Leadership, (2) Laissez-faire Leadership, and (3) Transformational Leadership. While there are three impacts of leadership that indeed to Phineas Taylor Barnum as the main character in The Greatest Showman, namely (1) Inspiring Confidence For Others, (2) Creating A Respectful Environment, and Raisings Loyalty and Trust. This movie shows many things to be a good leader who can bring a big impact on people. We are all leaders in our lives. So, this movie gives us so many things that we can learn to have a better life.